Perceptual and acoustic evaluation of speech production in Down syndrome: A case series. (1st February 2020) - O' Leary, Deirdre; Lee, Alice; O'Toole, Ciara; Gibbon, Fiona
ABSTRACT: People with Down syndrome (DS) can experience difficulties with speech production that can impact on speech intelligibility. In previous research, both perceptual and acoustic analysis has shown that people with DS can have difficulties with speech production in the areas of respiration, phonation, articulation, resonance and prosody. However, these studies have investigated various aspects of speech production separately. No study has examined all components of speech production in one single study and considered how these components, if impaired, may impact on speech intelligibility in DS. This paper presents the data of three male speakers with DS and three age- and gender-matched controls as a case series. The participants' speech samples were analysed using a number of perceptual and acoustic parameters, across the major components of speech production – respiration, phonation, articulation, resonance, and prosody. Results showed that different areas of speech production were affected in each participant, to different extents. The main perceptual difficulties included poor voice quality, monopitch, and monoloudness. Acoustic findings showed a higher mean F0, lower harmonics-to-noise ratio and longer voice onset times. These preliminary findings show that people with DS can present with mixed profiles of speech production that can affect speech intelligibility. When assessing speech production in DS, clinicians need to evaluate all components of speech production and consider how they may be impacting intelligibility.